Effect of Dolomite Addition on Fly Ash Based Ceramic Membrane to Reduce COD and BOD of Liquid Waste - Widiya Aprilianti; F. Widhi Mahatmanti; Mohammad Alauhdin; Jumaeri Jumaeri (Jurnal Kimia Sains dan Aplikasi, 2021)
Ceramic membrane technology plays an essential role in separation fields such as wastewater treatment. Fly ash as a membrane material has proven to be very effective for many separation processes, including water and air purification, as well as industrial and environmental resource recovery. This study aims to develop a microfiltration ceramic membrane based on fly ash with the addition of dolomite. The synthesized ceramic membranes were then characterized using XRD, SEM, and TGA. Ceramic membranes are used to reduce COD and BOD levels in tofu industrial wastewater. The results showed that the value of membrane porosity tends to increase with the addition of dolomite 0% (D0) to 30% (D30). The increase in the porosity value in the membrane was followed by a decrease in the average pore size, namely 1.6994 m at D0 and 1.1730 m at D30. The membrane with 30% dolomite composition has the best mechanical properties with a compressive strength of 35.29 MPa and superior thermal resistance. This is very beneficial for the use of membranes in the long term. Meanwhile, the membrane filtration ability and the ability of the membrane to reduce COD and BOD levels of waste increased with the addition of dolomite from 0% to 30%. However, the decrease in COD and BOD was smaller in the membrane with 45% dolomite. D30 membrane can reduce COD 80% and BOD up to 71.44%. D30 membrane is the most effective fly ash and dolomite composition in forming pores on the membrane with the best COD and BOD reduction performance.